THE IMPORTANCE OF PHONOLOGICAL AWARENESS FOR ENGLISH FOREIGN LANGUAGE STUDENTS - Yani Lubis; Gairah Rizki Harahap; Rizky Ummi Thahirah Nst; Ariqqah Raihana; Huda Hizkia Ahmad Siregar (Cahaya Ilmu Bangsa Institute, 2024)
Phonology may be a field of etymology that thinks about, analyzes and talks about arrangements of dialect sounds which are etymologically shaped from the words phon, to be specific sound, and logi, specifically science. Agreeing to the progression of sound units which are the question of consider, phonology is isolated into phonetics and phonemics. Within the learning prepare as a outside dialect. Each understudy must get an approach that emphasizes habituation and capacity (talking, perusing, composing and tuning in) to utilize the dialect they have learned. This article was composed utilizing subjective strategies based on library investigate. This could be translated as a investigate prepare carried out utilizing different scholarly sources or in this setting sources related to The Significance Of Phonological Mindfulness For English Outside Dialect Understudies as reference fabric. phonological mindfulness is vital for English as a Remote Dialect exceptionally youthful learners.